1995
DOI: 10.1038/hdy.1995.60
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism within and between populations of Ceratitis capitata: comparison between RAPD and multilocus enzyme electrophoresis data

Abstract: Random amplified polymorphic DNA (RAPD) analysis and multilocus enzyme electrophoresis (MLEE) were used to assess genetic variability in six wild populations and in five laboratory strains of Ceratitis capitata. The RAPD technique reveals larger amounts of genetic variation than the conventional MLEE, and can improve discrimination within and between populations and strains.In our experimental conditions, RAPD analysis with four different primers produces 174

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 23 publications
9
113
0
1
Order By: Relevance
“…The intermediate level of genetic variability shown by Ceratitis rosa corresponds to the medium level of geographical diffusion of this polyphagous species. During the dispersion processes C. capitata loses the greatest part of its variability (Baruffi et a!., 1995); its peripheral Mediterranean populations show levels of polymorphism comparable to the ones detected in Kenyan samples of T coffeae. No information is available on the genetic structure or dispersion of geographical populations of C. rosa and T coffeae.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The intermediate level of genetic variability shown by Ceratitis rosa corresponds to the medium level of geographical diffusion of this polyphagous species. During the dispersion processes C. capitata loses the greatest part of its variability (Baruffi et a!., 1995); its peripheral Mediterranean populations show levels of polymorphism comparable to the ones detected in Kenyan samples of T coffeae. No information is available on the genetic structure or dispersion of geographical populations of C. rosa and T coffeae.…”
Section: Discussionsupporting
confidence: 55%
“…In this context, Rhagoletis flies (R. pomonella species complex) have been at the centre of a discussion on sympatric speciation (Bush, 1966(Bush, , 1969Feder et a!., 1988Feder et a!., , 1990. Electrophoretic studies of genetic differentiation have provided a powerful tool for the analysis of sympatric speciation and phylogeny in Rhagoletis (Berlocher & Bush, 1982;Berlocher et a!., 1993), for resolving species complexes in the A. fraterculus group (Malavasi & Morgante, 1983;Steck, 1991) and in population genetic analysis in C. capitata (Gasperi et a!., 1991;Malacrida et al, 1992;Baruffi et aL, 1995). All of these studies suggest the great potential of genetic approaches for biogeographical and phylogenetic analysis of Tephritidae flies.…”
Section: Introductionmentioning
confidence: 99%
“…RAPD markers might also be able to retain a large part of the ancestral polymorphism. In a comparison between RAPDs and allozymes in the medfly, Baruffi et al (1995) revealed that invading populations showed a five-fold decrease in allozyme variation compared with ancestral populations, whereas RAPDs showed only a two-fold decrease. However, if we consider that only eight polymorphic markers were scored in A. pallipes from a set of 40 primers, this level appears very low compared to the RAPD variability already described for other animals in general (eg, Mamuris et al, 1999;Cooper, 2000).…”
Section: Colonization History Within Irelandmentioning
confidence: 99%
“…Genetic diversity F st or equivalent Population structure (cluster, …) Aagard et al, 1998 Allozymes Ͻ RAPDs Allozymes Х RAPDs Apostol et al, 1996 Allozymes Ͻ RAPDs Ayres and Ryan 1999 Allozymes Ն RAPDs a Regional scale concordance Bartish et al, 2000 Allozymes Ͻ RAPDs Allozymes Ͼ RAPDs Allozymes Х RAPDs Baruffi et al, 1994 Allozymes Wolf et al, 1998 Allozymes Ͻ RAPDs General congruence Haig et al, 1994 Allozymes Х RAPDs Allozymes RAPDs but neither resulted in overall assortment of clusters geographically Isabel et al, 1995 b Allozymes Х RAPDs Allozymes Х RAPDs Jenczewski et al, 1999 Allozymes Ͼ RAPDs Similar Agreement between the global patterns of populations structure Le Corre et al, 1997 Allozymes Ͼ RAPDs Allozymes Х RAPDs Allozymes RAPDs Liu and Furnier 1993 Allozymes Յ RAPDs* Mamuris et al, 1999 Allozymes Ͻ RAPDs Allozymes Ͻ RAPDs Isolation by distance observed in RAPDs, not in allozymes Oiki et al, 2001 Allozymes Ͻ RAPDs General congruence Peakall et al, 1995 Allozymes Ͻ RAPDs Large-scale concordance Puterka et al, 1993 Allozymes Ͻ RAPDs Allozymes Х RAPDs Allozymes Х RAPDs Ross et al, 1999 Similar Similar General congruence Sun et al, 1999 Allozymes Ͻ RAPDs Clustering pattern of isozymes has poorer discrimination power than for RAPDs Szmidt et al, 1996 b Allozymes Ͻ RAPDs Allozymes Х RAPDs Waycott, 1998 Allozymes Ͻ RAPDs Wu et al, 1999 Allozymes Ͻ RAPDs Allozymes Ͻ RAPDs Allozymes Х RAPDs a Depending on the species studied. Haploid tissue was analyzed in this study.…”
Section: Studymentioning
confidence: 99%